Lean Six Sigma and Innovation – an exploratory study among UK organisations. (2nd January 2016) - Antony, Jiju; Setijono, Djoko; Dahlgaard, Jens J.
Abstract : Although research has been carried out linking Total Quality Management and Innovation, it was found that there is a dearth of literature exploring the relationship between Lean Six Sigma (LSS) and Innovation. The purpose of this paper is to explore the link between LSS and Process/Product/Service Innovation. A number of interviews were carried out with 10 UK-based companies to explore how LSS and Process/Product/Service Innovation are linked. The interviewees (Six Sigma Black Belts and Master Black Belts) were carefully chosen to ensure that sound and valid conclusions could be derived from the investigation. Due to constraints of limited time, the number of people who participated in the study was relatively small. However, the authors argue that this study can provide a good foundation to various researchers and practitioners to further explore the nature of the relationship between one of the most popular business process improvement methodologies (LSS) and Process/Product/Service Innovation. Based on the interviews of 10 companies in the UK engaging with LSS initiatives, the authors found that LSS is commonly viewed as fostering Process/Product/Service Innovation, Incremental Innovation, or Innovation Capability. The authors also identify seven features specific to LSS that are likely to have significant influence on the above types of Innovation.